Processed Wood Factory to Address Energy Needs in Nepal - Khaniya, Sashank; Gautam, Bishnu Prasad (Journal of Engineering Technology and Planning, 2025)
With an increase in greenhouse gas emissions, growing challenges are faced in meeting the ever-increasing energy demands, both economically and environmentally. Many countries, including Nepal, rely heavily on imported fossil fuels to meet their energy demand. For example, Nepal spends more than 6% of its gross domestic product on petroleum imports, with liquefied petroleum gas comprising 20-25% of such imports. Although electricity is generated from renewable sources, its supply is not dependable to make electricity a primary source of cooking energy. Nepal is rich in forest resources, but they are vastly underutilized. While Nepal imports approximately 0.6 million tonnes of oil equivalent (Mtoe) of LPG gas annually, Nepal’s wood resources have an estimated annual theoretical potential of 7.1 Mtoe of energy. This review paper presents the current status of energy production and consumption in Nepal, along with the status of forest resources, with a focus on utilizing the abundant wood resources. A novel approach is presented to tackle Nepal’s energy deficit by supplementing through underutilized forest resources, encouraging the use of cleaner firewood, reducing imports of liquefied petroleum gas, and ultimately curbing carbon emissions. This review demonstrates that forest rich countries like Nepal can devise improved technology by utilizing forest-based sources while their population is transitioning from conventional sources to industrial products. A pilot project is proposed to produce seasoned firewood equivalent to 334 toe of energy annually, which may substitute 304 tonnes of liquefied petroleum gas imports, thus lowering the emissions by 882 tonnes of carbon dioxide equivalent.